Corrected Hawking temperature of acoustic rotating black hole - Mahanta, Chandra Rekha; Misra, Rajesh (International Journal of Advanced Astronomy, 2015)
In this paper, the corrected Hawking temperature of (2+1) dimensional acoustic rotating black hole has been calculated by using tunneling method. For this purpose, the r-t sector of the metric is isolated from the angular part by taking a transformation of the time and the azimuthal angle co-ordinates in the exterior region of the event horizon. The massless particle of this black hole obeys the Klein- Gordon equation of motion.